Comment on “Han Fu culture: the emphasis on Chinese traditional cultural identity” - Miao Yu (Trans/Form/Ação)
Commented article: YU, Q. Han Fu culture: the emphasis on Chinese traditional cultural identity. Trans/Form/Ação: Unesp journal of philosophy, Marília, SP, v. 47, n. 5, p. e02400157, 2024. Available at: https://revistas.marilia.unesp.br/index.php/transformacao/article/view/15081.